Regional Workshop on Pesticide Management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
DG Hunter and M Umar. 1998. 18 pp.ISBN 982 175 141 5Institute for Research, Extension and Training in Agriculture (IRETA), University of the South Pacific, Alafua CampusPrivate Mail Bag, Apia, Western Samoa.Fax: +685 223 47Email:...